Teaching social science research methods in an online setting: pointers from a literature review - Kirss, Laura; Hunt, Pihel; Kalk, Karmen (Przegląd Krytyczny, 2022)
Social science research methods are being increasingly taught in an online setting. The COVID-19 pandemic has been a major driver of this trend recently. Although there has been extensive research on online teaching and learning in general, very few studies focus on how this needs to be done specifically in social science research methods (SSRM). This literature review summarizes the most current research evidence on SSRM teaching in an online setting. Such information can facilitate setting up future online teaching and learning activities regarding social science research methods. In addition, the article discusses how this knowledge can be transferred to a practical SSRM online teaching and learning tool (a toolbox in the Navigating Social Worlds project).